The influence of adaptive challenge on engagement of multidisciplinary staff in standardising aseptic technique in an emergency department: A qualitative study. Issue 3 (2nd December 2019) - Towell‐Barnard, Amanda; Slatyer, Susan; Cadwallader, Helen; Harvey, Michelle; Davis, Susan
Abstract: Aims and objectives: To explore the challenge of engaging multidisciplinary staff in standardising aseptic technique (AT) in an emergency department (ED) in an Australian tertiary hospital, and to better understand the enablers and barriers to implementing practice change within this setting. Background: Healthcare‐associated infections are the most common complication for patients in acute care. A clinical practice framework developed in the United Kingdom (UK) standardised AT practice to reduce potential infection risk. One Australian tertiary hospital drew upon this framework to similarly improve clinical practice. It was understood that standardising practice would require some practitioners only to revisit and demonstrate AT principles already embedded in their practice, while others would be challenged to adopt a new approach. Design: Qualitative, descriptive research design. Methods: Data were collected through focus groups held before and after implementation of the AT programme. Data were analysed using the framework method. The (COREQ) checklist was followed. Results: Four emergent themes described the influence of motivation on individuals' beliefs and attitudes towards practice change, relationships within the ED context, delivery of education and management directives. Conclusion: Implementing practice change is more than just providing technical knowledge and includes changing individuals' beliefs and attitudes. An understanding of adaptive challenge can assist in implementing practice change that involves the multidisciplinary team. Relevance to clinical practice: Results provide evidence as to how the adaptive challenge framework could be a suitable approach to manage potential enablers and barriers to implementing change within a multidisciplinary team in an acute hospital.